New challenges in therapeutic vaccines against HIV infection. (3rd June 2017) - Leal, Lorna; Lucero, Constanza; Gatell, Josep M; Gallart, Teresa; Plana, Montserrat; García, Felipe
ABSTRACT: Introduction : There is a growing interest in developing curative strategies for HIV infection. Therapeutic vaccines are one of the most promising approaches. We will review the current knowledge and the new challenges in this research field. Areas covered : PubMed and ClinicalTrial.gov databases were searched to review the progress and prospects for clinical development of immunotherapies aimed to cure HIV infection. Dendritic cells (DC)-based vaccines have yielded the best results in the field. However, major immune-virologic barriers may hamper current vaccine strategies. We will focus on some new challenges as the antigen presentation by DCs, CTL escape mutations, B cell follicle sanctuary, host immune environment (inflammation, immune activation, tolerance), latent reservoir and the lack of surrogate markers of response. Finally, we will review the rationale for designing new therapeutic vaccine candidates to be used alone or in combination with other strategies to improve their effectiveness. Expert commentary : In the next future, the combination of DCs targeting candidates, inserts to redirect responses to unmutated parts of the virus, adjuvants to redirect responses to sanctuaries or improve the balance between activation/tolerance (IL-15, anti-PD1 antibodies) and latency reversing agents could be necessary to finally achieve the remission of HIV-1 infection.